Early evaluation of experiences of health care providers in reception centers with a patient-held personal health record for asylum seekers: a multi-sited qualitative study in a German federal state - Jahn, Rosa; Ziegler, Sandra; Nöst, Stefan; Gewalt, Sandra Claudia; Straßner, Cornelia; Bozorgmehr, Kayvan (Globalization and health, 2018)
The provision of high-quality medical care to asylum seekers represents a key challenge in many countries of the European Union. Especially continuity of care has been difficult to achieve as the migrant trajectory moves asylum seekers across and within European countries. Patient-held personal health records (PHR) have been proposed to facilitate the transfer of medical history between health sectors and providers, but so far there is no data to support its use in the migrant setting. The present paper addresses this knowledge gap by exploring the experiences and practices of healthcare providers in reception centers for asylum seekers using a patient-held PHR as well as the perceived associated benefits and shortcomings.